CAMPUS STUDENT EFFORTS TO TEACH TO DEVELOP CHARACTER OF ELEMENTARY SCHOOL STUDENTS THROUGH CHILD-FRIENDLY EDUCATION - Anwar, Rosyida Nurul (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The development of student character through religious values ​​is a necessity and a necessity. Child-friendly education is a way to grow student character. Child-friendly education is carried out by teachers and all parties related to student character development. This study aimed to determine the role of campus students teaching class three in shaping student character in the education unit where students are assigned. The study used a descriptive qualitative approach. The research subjects were 30 elementary school students. The research was conducted at the school that was the teaching campus's target, SD Negeri Rejosari 02, East Java. The results showed that the efforts of Campus Teaching students in developing student character through child-friendly education, providing motivation to maintain good consistency, through habituation, utilizing school facilities, and civilizing 5S. Student character becomes an important thing to be developed in students. To create a better future generation.